Interface features of SiO₂/SiC heterostructures according to methods for producing the SiO₂ thin films - Bacherikov, Yu.Yu.; Boltovets, N.S.; Konakova, R.V.; Kolyadina, E.Yu.; Ledn’ova, T.M.; Okhrimenko, O.B. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2012)
In this work, we studied comparative characteristics of the SiO₂/SiC heterostructures. The following two techniques were used for SiO₂ formation: thermal oxidation in water vapor (i) and oxidation in solution (ii). According to experimental results obtained from optical absorption and photoluminescence spectra as well as from measurements of internal mechanical stresses, one can conclude that the thin SiO₂ films prepared using the technique (ii) possess SiO₂/SiC interface with a less number of defective states than that for SiO₂ films prepared using the technique (i).